Cognitive behavioral game design: a unified model for designing serious games - Starks, Katryna (Frontiers in Psychology, 2014)
Video games have a unique ability to engage, challenge, and motivate, which has led teachers, psychology specialists, political activists and health educators to find ways of using them to help people learn, grow and change. Serious games, as they are called, are defined as games that have a primary purpose other than entertainment. However, it is challenging to create games that both educate and entertain. While game designers have embraced some psychological concepts such as flow and mastery, understanding how these concepts work together within established psychological theory would assist them in creating effective serious games. Similarly, game design professionals have understood the propensity of video games to teach while lamenting that educators do not understand how to incorporate educational principles into game play in a way that preserves the entertainment. Albert Bandura’s (1998) social cognitive theory (SCT) has been used successfully to create video games that create positive behavior outcomes, and teachers have successfully used Howard Gardner’s (1983) theory of multiple intelligences (MI) to create engaging, immersive learning experiences. Cognitive behavioral game design is a new framework that incorporates Social Cognitive Theory (SCT) and Multiple Intelligences (MI) with game design principles to create a game design blueprint for serious games.